Videothoracoscopic management of hemoptysis due to anomalous bronchial vessel treated with multiple bronchial artery embolizations: a case report - Gismondi, Alice; Frediani, Simone; Pardi, Valerio; Pietro Aloi, Ivan; Bertocchini, Arianna; Accinni, Antonella; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Introduction: Hemoptysis is an alarming clinical presentation caused by a vast number of primitive conditions (infectious, malignancies, malformations, vasculitis). However, at the root of hemoptysis, there is always a "noxa patogena" altering vessel structure, usually bronchial arteries, which are characterized by high pressure.Bronchial artery embolization (BAE) is the first-line treatment for hemoptysis for its technical and clinical success, although the long-term overall outcome is not equally adequate.Case Report: A 12-year-old boy was referred to our hospital for massive hemoptysis after a history of recurrent episodes since the age of 3. The patient had been diagnosed with bilateral and widespread bronchial artery hypertrophy at another hospital and treated with several BAE procedures. We performed BAE to stabilize the child as well as an angio-CT scan, which confirmed the presence of the recently placed coil to embolize a hypertrophic bronchial arteriosus branch originating from the left thyrocervical trunk and directed to the right lower lobe. Results of previous embolization (metal coils) were found at the origin of the right inferior thyroid artery and the right costo-cervical trunk. After 21 months since his first admission to our hospital, the patient was transferred by air ambulance for a massive hemoptysis recurrence. Further BAE of the previously coiled vessel coming from the right succlavia (and right inferior thyroid artery) was impossible to perform due to the presence of the coils positioned in the past. A thoracoscopic approach was chosen: the previously identified anomalous vessel was isolated and ligated using double metal clips, two on both the proximal and distal sides.Accurate exploration of the thoracic cavity was accomplished, verifying the absence of collateral vessels coming from the diaphragmatic side. The patient was discharged in four days in good clinical.Discussion: Although bare-minimum invasive embolism (BAE) is still the gold standard for treatment, there are situations when it may not produce the desired clinical outcome and increase the risk of rebleeding. In these situations, minimally invasive surgical procedures using a videothoracoscopic approach can be beneficial if there is a suspicion of an aberrant vessel on a DSA or CT scan.